Policy-induced market distortions along agricultural value chains: Evidence from Ethiopia and Nigeria - Allen, Summer L.; Kassie, Girma T.; Majeed, Fahd; Tokgoz, Simla (International Food Policy Research Institute, 2021)
The performance of agrifood value chains of vital importance for smallholder farmers in developing countries. Measuring and understanding how government policies, such taxes, subsidies, minimum support prices, and government procurement, impact particular value chains is essential to minimize unintended consequences for value chain actors. This analysis of distortions in value chains in Ethiopia (sheep and goats) and Nigeria (cacao and palm oil) uses nominal rates of protection (NRPs) to measure the impact of policies on domestic prices for producers and consumers. Using the NRP methodology is effective for highlighting the significant impact of agricultural policies on prices from the local to the country level and along entire agrifood value chains.